1994
DOI: 10.1084/jem.180.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Anti-immunoglobulin E treatment decreases worm burden and egg production in Schistosoma mansoni-infected normal and interferon gamma knockout mice.

Abstract: The immunoglobulin E (IgE) response is generally considered an essential component of the host defense against parasitic helminths such as Schistosoma mansoni. In contrast, work on antischistosome vaccines suggests that interferon gamma (IFN-gamma) is the critical immune mediator for vaccine-induced immunity to the parasite. In this study, the total IgE response to a primary S. mansoni infection was suppressed by anti-IgE treatment in both normal mice and in mice with defective IFN genes (gene knockout [GKO]).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 42 publications
(35 reference statements)
2
44
2
2
Order By: Relevance
“…Furthermore, administration of an anti-IL4 antibody to the high-IgE responders, which knocks out their IgE response, reduces their mortality to that of the low responding group (39). Similarly another study demonstrated that anti-IgE treatment was beneficial in Schistosoma infected mice (40). Some authors have suggested that atopy may protect against the development of neoplasia (41,42) but others have failed to corroborate these findings (43,44) and they relate the diminished risk of cancer to atopy and not specifically to IgE levels.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, administration of an anti-IL4 antibody to the high-IgE responders, which knocks out their IgE response, reduces their mortality to that of the low responding group (39). Similarly another study demonstrated that anti-IgE treatment was beneficial in Schistosoma infected mice (40). Some authors have suggested that atopy may protect against the development of neoplasia (41,42) but others have failed to corroborate these findings (43,44) and they relate the diminished risk of cancer to atopy and not specifically to IgE levels.…”
Section: Discussionmentioning
confidence: 74%
“…Nevertheless, there is considerable controversy concerning the role of IgE in the host-parasite relationship based on the work in humans and other experimental models (Hagan 1993, Capron & Capron 1994, Cutts & Wilson 1997, Webster et al 1997. Controversial findings have also been published concerning the biological role of IgE within the experimental model of the primary murine S. mansoni infection (Amiri et al 1994). IgE is thought to represent a major defence component against schistosomiasis, presumably by targeting the effector cells against the invading larvae in antibody-dependent cell-mediated reactions.…”
Section: Immune Response In Undernourished Mice Infected With S Mansonimentioning
confidence: 99%
“…treatment with anti-IgE, has been reported to inhibit the development of S. mansoni suggesting that the worms need this immunoglobulin for normal development (Amiri et al 1994). This is difficult to reconcile with the increased numbers of worms developing in IgE ko mice ) and the normal development of worms in FcεRI ko mice, in B cell ko mice and in SJA/9 mice unable to produce IgE , El Ridi et al 1998.…”
Section: Worm Development Fecundity and Fecal Egg Excretionmentioning
confidence: 99%